DESIGN AND IMPROVEMENT OF ALGORITHMS FOR AUTONOMOUS MOBILE ROBOT - CHIN, CHIN HAN SHEN (Universiti Teknologi Petronas, 2013)
Autonomous mobile robot (AMR) without human operators has been required in different part of industry. The robot has to be intelligent and able to decide their own action in order to assist human in completing tasks or eventually replace human. This project focuses on design and improvement of the motion control algorithms for autonomous mobile robot in line following. This project use Freescale MPC5604B as microcontroller and linear optical sensor to obtain line information. Simple PID algorithms will be used to improve the speed stability of the dc motor and control motion of servo motor in steering the robot along the line. By applying PID algorithms, the robot’s speed and direction can be in closed-loop control. In order to increase speed and reliability of the robot, hardware and software test are carried out. This concept can be applied in autonomous vehicle to improve the movement control and responses in any environment.